Understanding the impacts of biotechnology: a survey among the university students in chittagong - Tasnim, Nishat (Brac University, 2024)
This thesis submitted to the Department of Mathematics and Natural Sciences in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2024.